Escravos e escravatura em Moçambique. Problemas identitários - Martins, José Soares (Africana Studia, 2020)
The substantial differences among colonial Moçambique slave systems produced a wide range of morphological and semantic equivocation. This paper intends to define the concept of slave as also typi:ty the different social formations in the colonial Moçambique.